Analisa Pengendalian Banjir Kali Ciliwung Ruas Jembatan MT. Haryono – Pintu Air Manggarai - Zamroni, Fahmi; Sholichin, Moh.; H., Andre Primantyo (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2015)
Flooding is an annual problem occurs in DKI Jakarta. Generally the cause of flooding in Jakarta happened because of two major factors, the natural factor that flooding is influenced by 13 rivers that cross the DKI Jakarta and the human factor that changes the function areas border the river.In this study made seven simulations of alternative flood control at Ciliwung River segment MT. Haryono to Manggarai Sluice with flood plan discharge 100 years. Furthermore the most optimum alternative is determined taking into account the volume of runoff occurring and the budget plan costs.Based on analysis of the hydraulics and analysis of budget plan costs obtained that the most optimum alternative is the normalization of Ciliwung River segment MT. Haryono to Manggarai Sluice. The volume on the main channel is 1.730.520 m 3 and overflow did not occur. High water level at observation point P-174 and P-1 respectifely are +14,05 m and +8,76 m the average water level lossis 4,57 m with construction costs 694.668.698.520,55 IDR.Keywords :Flood control, Ciliwung River, reduction of overflow, cost.